Timepiece component comprising substrate made of glass transparent to visible light and having improved tensile strength

By applying an electronic grade passivation layer on the surface of the glass assembly, the mechanical performance degradation caused by defects and environmental humidity of the small glass assembly is solved, and the high fracture resistance and mechanical strength of the assembly are achieved.

CN119487458APending Publication Date: 2025-02-18ASSOC SUISSE POUR LA RECH HORLOGERE ASRH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051696.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When manufacturing small glass components, defects such as scratches, microcracks and micropores lead to a decrease in the mechanical properties of the glass, especially in the face of ambient humidity and OH-ions, crack propagation accelerates, resulting in component failure.

Method used

An electronic passivation layer is used to coat the surface of the glass substrate to reduce the surface density of point defects and isolate it from the ambient humidity to prevent OH-ions from entering, thereby improving the mechanical properties of the glass.

Benefits of technology

Through the use of the passivation layer, the crack resistance and mechanical strength of the glass assembly are significantly improved, crack expansion is reduced, and the service life of the assembly is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487458A_ABST
    Figure CN119487458A_ABST
Patent Text Reader

Abstract

The invention relates to a timepiece component (10) with improved tensile strength, comprising a substrate (20) made of glass transparent to visible light and having a lateral dimension of about several centimeters or less and a thickness of about 5 millimeters or less. The substrate (20) is coated with a passivation layer (30) in direct contact with the surface (25) of the substrate (20), having a thickness of less than 1000 nm. The passivation layer (30) comprises a refractory ceramic comprising at least 1 atomic% hydrogen. The invention also relates to a method for producing such an assembly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a watch component comprising a glass substrate transparent to visible light and having improved resistance to breakage, and a method of manufacturing the same. Background Art

[0002] Amorphous fused silica or vitreous silica (SiO 2 ) has the theoretical potential to achieve very high mechanical properties, which are defined by the Si-O interaction strength (fracture strength potential calculated at 17 GPa). In practice, the mechanical properties of vitreous silica are reduced by the presence of defects (scratches, microcracks, micropores, inclusions, etc.). These defects are usually caused during the molding of the vitreous silica component. These defects are usually the cause of slow crack growth. Slow crack growth can be compared to stress corrosion, which is caused by the presence of OH- ions in the ambient humidity, accelerating the expansion of cracks, which is the microscopic cause of failure of brittle materials. Since small components have fewer defects statistically, the miniaturization of components reduces the possibility of millimeter defects (scratches, microcracks). Therefore, the use of vitreous silica is more interesting for the manufacture of small components such as in the case of micromechanical and watchmaking components, such as millimeter or sub-centimeter components.

[0003] Despite the beneficial potential of reducing the size of mechanical components to exploit the properties of vitreous silica, the inevitable increase in the surface-to-volume ratio and the effect of slow crack propagation necessitate the implementation of solutions capable of reducing the surface density of defects and preventing (or at least reducing) the ingress of ambient moisture (especially OH- ions) into the components.

[0004] Furthermore, passivation layers for electronic devices of single-crystal materials commonly used in optoelectronic applications (in particular: silicon, GaAs, etc.) have been developed whose main technical feature is the perfection of the single-crystal lattice necessary to ensure optimal device operation. In these application areas, current device performance is limited by the presence of defects (usually atomic) on the surface or at the interface.

[0005] In the field of electronic components (transistors) and photovoltaic (PV) devices based on single crystal silicon, it is well known that atomic defects on the surface and / or at the crystal interfaces are the performance determining factor when component dimensions are reduced or, as in PV applications, when the volumetric defect density in the material is not significant.

[0006] The various passivation solutions developed in the electronics and PV sectors based on single-crystal silicon consist in coating the surface of the active volume with a thin, usually amorphous layer consisting of amorphous silicon (a-Si:H), silicon oxide (SiO2), silicon carbide (SiC), silicon nitride (Si3N4) or a combination thereof (e.g. oxynitride, silicon oxycarbide) or a combination thereof (e.g. SiO2+Si3N4) or a stacking sequence thereof (e.g. oxynitride, silicon oxycarbide) or a combination thereof (e.g. SiO2+Si3N4) or a stacking sequence thereof.

[0007] To limit the ingress of ambient humidity, glass components can be coated with a kerosene layer or a polymer coating (Parylene, ORMOCER, etc.). However, these types of coatings are not suitable for the tribological stresses to which the component surface must respond in micromechanical and watchmaking applications.

[0008] A type of glass that is more resistant to slow crack growth than vitreous silica may also be used, such as aluminosilicate or borosilicate glasses. Summary of the invention

[0009] One object of the present invention is to apply an electronic grade passivation layer to improve the mechanical properties of glass transparent to visible light in millimeter to sub-centimeter level components. Here, the term "glass" refers to an amorphous or nanocrystalline material. The expression "transparent to visible light" means transparent within a sufficient range of the wavelength range between 0.38 mm and 0.78 mm to enable the human eye to perceive the presence of the background. In the remainder of this disclosure, glass transparent to visible light will be simply referred to as "glass". Such glass is of interest in the field of watchmaking, particularly in designing aesthetic components with high rigidity and environmental stability.

[0010] Another object of the present invention is to improve the mechanical properties of transparent glass, such as fracture strength, for use in micro-components of millimeter to sub-millimeter size, such as watch components.

[0011] According to the invention, these objects are achieved in particular by a passivation layer on the surface of the component in order to reduce the surface density of point defects (e.g. disordered or under-ordered bonds) and to isolate the component from moisture (OH-ions) of atmospheric origin which is responsible for accelerating crack propagation leading to failure.

[0012] More specifically, the present invention relates to a watch component with improved fracture resistance, comprising a glass substrate having lateral dimensions of the order of centimeters or less and a thickness of the order of millimeters or less. The substrate is coated with a passivation layer, the passivation layer being in direct contact with the substrate surface and having a thickness of less than 1000 nm, preferably less than 600 nm or more preferably less than 400 nm. The passivation layer comprises a refractory ceramic, the refractory ceramic comprising at least 1 atomic % hydrogen.

[0013] The low thickness of the passivation layer allows components to have high dimensional accuracy. This is particularly advantageous in micromechanical and watchmaking applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] An example of implementation of the invention is indicated in the description illustrated by the accompanying drawings, in which:

[0015] Figure 1 schematically illustrates a micromechanical component including a substrate having a passivation layer according to one embodiment;

[0016] Figure 2 A schematic cross-sectional view showing a substrate surface according to one embodiment;

[0017] Figure 3 Demonstrating bending strength testing of glass discs by B3B test; and

[0018] Figure 4 Shown is a mesoscale 3-point flexural strength test performed in a micro test. DETAILED DESCRIPTION

[0019] Figure 1 The watch component 10 is schematically shown, comprising a substrate 20 of glass transparent to visible light, having lateral dimensions of the order of a few centimeters or less and a thickness of the order of a millimeter or less. The substrate 20 is coated with a passivation layer 30, which is in direct contact with the surface 25 of the substrate 20.

[0020] The glass may comprise vitreous silica or a glass containing vitreous silica.

[0021] According to one embodiment, the passivation layer 30 has a thickness of less than 1000 nm, preferably less than 600 nm, or more preferably less than 400 nm.

[0022] The passivation layer 30 comprises a refractory ceramic comprising at least 1 atomic % of hydrogen.

[0023] The passivation layer 30 reduces the defect density of the substrate 20, in particular improving the impact resistance. The passivation layer also isolates the substrate 20 (and therefore the component 10) from the ambient humidity and therefore from the OH- ions present in the atmosphere, which are responsible for accelerating the propagation of cracks leading to fracture. Depending on the choice of its chemical composition, the passivation layer 30 can also be used to maintain the aesthetic appearance (invisibility, transparency) of the initial component 10 machined into the substrate 20.

[0024] The choice of one or other of the chemical composition of the passivation layer 30 and its thickness may also depend on the desired properties of the coating, such as electrical resistance on the substrate, suitability for charge transport, transparency, consistency, deposition temperature, hardness, chemical barrier to ion migration, tribological behavior, chemical compatibility with lubricants, etc.

[0025] In one embodiment, the refractory ceramic comprises one of hydrogenated silicon oxynitride (SiON:H), hydrogenated silicon oxycarbide (SiOxCy:H), hydrogenated silicon carbide (SiC:H), hydrogenated silicon nitride (Si3N4:H), or a combination thereof.

[0026] The refractory ceramic passivation layer 30 comprising SiON:H, SiOxCy:H, SiC:H or Si3N4:H ceramic or a combination of these ceramics ensures visual transparency of the layer and is hermetically sealed to prevent the transport of ions, especially OH- ions, to the substrate 20.

[0027] A hydrogen content of the order of several atomic percent saturates defects formed by unsaturated atomic bonds on the surface 25 of the substrate 20. For example, on the surface 25 of a single crystal silicon substrate, hydrogen reduces the density of dangling bonds. The importance and role of hydrogen passivation are exploited in the semiconductor electronics industry and photovoltaic applications. In the present invention, the passivation layer 30 comprising a refractory ceramic containing at least 1 atomic percent hydrogen improves the fracture toughness of the component 10.

[0028] In the case of brittle materials, such as the glass constituting the substrate 20 , the resistance to fracture is inversely proportional to the density of defects, potentially at the origin of microcracks, the propagation of which would lead to failure of the assembly 10 .

[0029] The passivation layer comprising a refractory ceramic containing at least 1 atomic % hydrogen reduces the surface density of defects on the surface 25 of the substrate 20. The reduction in the surface density of defects increases the mechanical strength of the component 10, and in particular the fracture resistance.

[0030] A thickness of less than 1000 nm, less than 600 nm, or less than 400 nm enables the passivation layer 30 to act as a barrier to the penetration of impurities that catalyze or accelerate the growth of microcracks, such as OH − ions in the vitreous silica substrate 20 .

[0031] The performance of the passivation layer 30, in particular the reduction of the surface defect density of the substrate 20 and the isolation of the substrate 20 from ambient humidity, depends on the surface condition 25 of the substrate 20. For example, the surface 25 of the substrate 20 must not be affected by mechanical processing. Therefore, defects on the surface 25 of the substrate 20, such as scratches and microcracks, should be eliminated or at least minimized.

[0032] In one embodiment, the surface 25 of the substrate 20 on which the passivation layer 30 is formed is smoothed or polished to a roughness Ra of less than 100 nm. Figure 2 A schematic cross-sectional view of the surface 25 is shown. Preferably, the surface 25 is flattened so that the surface 25 of the substrate 20 has a surface topology comprising asperities 27 or rounded depressions with a radius of curvature greater than 500 nm, preferably greater than 4 μm. The flat surface 25 has no facets or sharp corners that may lead to possible concentrations of stress during mechanical loading.

[0033] Preferably, the surface 25 of the substrate 20 should also be clean, i.e., have a controlled surface chemistry. Such a controlled surface chemistry may mean that the surface 25 of the substrate 20 is substantially free of particle contamination, native oxides (due to moisture and oxygen in the air), organic matter, coating residues, inorganic bases or acids, or other metal contamination. In other words, the chemical composition at the surface 25 is as close as possible to the mass chemical composition of the substrate 20.

[0034] The flexural strength tests were performed on glass disks with a diameter of 10 mm and a thickness of 0.2 mm. The glasses used included aluminosilicate glass, borosilicate glass and vitreous silica. The disks were polished on both sides by optical quality polishing resulting in a roughness Ra of less than 1 nm. Disks with a SiON:H passivation layer 30 of 400 nm thickness and without a passivation layer 30 were measured. The flexural strength tests were performed using the "three ball on ball" (B3B) test. The results of these tests performed in air for 30 disks are shown in Figure 3 middle.

[0035] exist Figure 3 In FIG. 1 , the arrows show the effect of the passivation layer on the flexural strength B3B distribution for a vitreous silica disk with a SiON:H passivation layer and a thickness of 400 nm.

[0036] Mesoscale 3-point bending fracture tests were also performed on microtubes with a 0.2 mm square cross section. 2 Wafer machining of microtubes. This mechanism is necessary to obtain a machined surface of sufficient quality in terms of defects and residual machining stresses. The results of the mesoscale 3-point bending test are shown in Figure 4 middle.

[0037] exist Figure 4In Figure 1, the fracture toughness distribution of microtubes machined using the spark assisted chemical engraving (SACE) method is plotted. The unpassivated specimens were mechanically stressed with a paraffin coating (SACE-paraffin). The passivated specimens (SACE-passivated) feature a 400nm SiON:H passivation layer and are loaded in air. Mechanical stress is applied to the machined surface. The passivation layer is considered functional if the mechanical properties measured on the passivated specimens in air are at least equal to those measured on the paraffin-coated specimens. The beneficial effect of passivation on the mechanical properties can also be seen in the narrowing of the fracture strength distribution.

[0038] Figure 3 and 4 The results show that for both initial surface states of vitreous silica, ie the optically polished surface 25 with Ra<1 nm for the B3B test and the mechanically processed surface 25 for the mesoscale test, the passivation layer 30 improves the mechanical properties.

[0039] In particular, the minimum strength of the specimens was improved. Statistical analysis of B3B results ( Figure 3 ) shows that the average fracture toughness of the passivated vitreous silica disks polished on both sides increased by 25%. The results also show a narrower distribution of fracture toughness of the samples.

[0040] In the case of bending tests carried out on discs in the B3B configuration, two thicknesses of the passivation layer 30 were evaluated. Analysis of these results shows that the thickness of the passivation layer 30 should preferably be equal to or less than 400 nm.

[0041] Studies on the uniformity of the growth of the passivation layer 30 (covering the same layer thickness on the protruding or recessed elements in the component) have shown that all the surfaces of the component 10 that bring together the characteristic watchmaking elements (such as escapement teeth, holes (diameter 3 mm to 0.2 mm), elongated beams, tongues, points and recessed elements) are satisfactorily coated with the passivation layer 30.

[0042] The substrate 20 may be coated with a passivation layer 30 on one, several or all surfaces 25 thereof. Preferably, the passivation layer 30 may be formed on all surfaces 25 of the substrate 20. Even more preferably, the three-dimensional component 10 has a passivation layer 30 of substantially uniform thickness on all surfaces 25 thereof.

[0043] In one embodiment, the watch component may include a display component or an external component.

[0044] According to one embodiment, a method of manufacturing watch assembly 10 comprises the following steps:

[0045] machining the glass to form a substrate 20 having lateral dimensions on the order of centimeters or less and a thickness on the order of millimeters or less; and

[0046] A passivation layer 30 is formed on the surface 25 of the substrate 20 , the passivation layer 30 having a thickness of less than 1000 nm and comprising a refractory ceramic comprising at least 1 atomic % of hydrogen.

[0047] The passivation layer 30 can be formed by a chemical vapor deposition method. In particular, the passivation layer 30 can be formed by a plasma assisted chemical vapor deposition (PECVD) method, which is dedicated to three-dimensional uniform coating of the component 10. For example, the passivation layer 30 can be formed in a reactor containing a rotation / mixing / return device, which promotes uniform deposition of the passivation layer 30 on one or more three-dimensional components 10, as described in Swiss patent application CH715599. In order to ensure that the deposition of the passivation layer 30 does not cause additional defects on the surface 25, low temperature, gentle coating methods such as thermal growth or PECVD layer deposition are preferred.

[0048] In one embodiment, before the step of forming the passivation layer 30 , the method may further include a step of dissolving the surface 25 of the substrate 20 in a chemical vapor phase or a liquid phase.

[0049] The step of machining the substrate 20 may include selectively chemically dissolving the substrate 20 and releasing the machined component 10 .

[0050] According to one embodiment, the mechanical processing step may include one of the following processes: deep reactive ion etching (DRIE), spark assisted chemical engraving (SACE) or very short pulse laser marking (femtosecond to picosecond). The mechanical processing step may optionally be followed by selective chemical dissolution of the marking volume (or selective laser engraving).

[0051] Other machining methods may also be used within the scope of the invention, such as light induced deep etching (LIDE) or selective laser etching (SLE), all of which include a chemical dissolution step for releasing the machined component 10 .

[0052] According to one embodiment, the method comprises the steps of smoothing and / or flattening the surface 25 of the substrate 20 to obtain rounded asperities or depressions with a radius of curvature greater than 500 nm, preferably greater than 4 μm. The smoothing and / or flattening step may also comprise polishing the surface 25 receiving the passivation layer 30. Preferably, the polishing is performed with an optical quality resulting in a roughness Ra of less than 1 nm. The step of smoothing and / or flattening the surface 25 is performed before forming the passivation layer 30.

[0053] In one embodiment, the method includes a surface cleaning step performed before forming the passivation layer 30 to achieve a controlled chemical state of the surface, i.e., the surface 25 is substantially free of contamination by particles, native oxides (due to humidity and oxygen in the air), organic matter, layer residues, inorganic bases or acids, or other metal contaminants. The surface cleaning step is performed before forming the passivation layer 30.

[0054] Reference numerals used in the drawings

[0055] 10 Components

[0056] 20 Substrate

[0057] 25 Surface

[0058] 27 Roughness

[0059] 30 Passivation layer

Claims

1. A watch component (10) having improved breakage resistance, comprising A glass substrate (20) which is transparent to visible light and has lateral dimensions on the order of a few centimeters or less and a thickness on the order of a millimeter or less; The substrate (20) is coated with a passivation layer (30) which is in direct contact with a surface (25) of the substrate (20) and has a thickness of less than 1000 nm, the passivation layer (30) comprising at least one refractory ceramic comprising at least 1 atomic % of hydrogen.

2. The component according to claim 1, wherein the passivation layer (30) has a thickness of less than 600 nm and preferably less than 400 nm.

3. The component according to claim 1 or 2, wherein the refractory ceramic comprises hydrogenated silicon oxynitride (SiON:H), hydrogenated silicon oxycarbide (SiOxCy:H), hydrogenated silicon carbide (SiC:H), hydrogenated silicon nitride (Si3N4:H) or a combination of these ceramics and stacks thereof.

4. The component according to any one of claims 1 to 3, wherein the surface (25) of the substrate (20) has a roughness Ra of less than 100 nm.

5. The component according to claim 4, wherein the surface (25) of the substrate (20) comprises asperities having a radius of curvature exceeding 4 μm.

6. The component of any one of claims 1 to 5, wherein the glass comprises vitreous silica or a glass containing vitreous silica.

7. The component according to any one of claims 1 to 6, comprising a mechanically stressed component.

8. A component according to any one of claims 1 to 7, comprising a component of a display device or an external watch part.

9. A method for manufacturing a watch component according to any one of claims 1 to 8, the method comprising the following steps: Mechanically processing the glass to form a substrate (20) having lateral dimensions on the order of centimeters or less and a thickness on the order of millimeters or less; The passivation layer (30) is formed on the surface of the substrate (20), the passivation layer (30) having a thickness of less than 1000 nm and comprising at least one refractory ceramic containing at least 1 atomic % of hydrogen.

10. The method according to claim 9, wherein the passivation layer (30) is formed by a chemical vapor deposition method.

11. The method according to claim 10, wherein the passivation layer (30) is formed by a plasma assisted chemical vapor deposition (PECVD) method.

12. The method according to any one of claims 9 to 11, comprising the following steps: The surface (25) of the substrate (20) is smoothed and / or planarized so as to obtain a surface topology comprising asperities (27) having a radius of curvature exceeding 500 nm, preferably exceeding 4 μm.

13. The method according to any one of claims 9 to 12, further comprising a step of chemically dissolving the surface of the substrate (20) in a gas phase or a liquid phase before the step of forming the passivation layer (30).

14. The method according to any one of claims 9 to 13, wherein the step of machining the substrate (20) comprises selectively chemically dissolving the substrate (20) and releasing the machined component (10).